2002
DOI: 10.1002/neu.10160
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental influences on human psychological differences

Abstract: Psychological researchers typically distinguish five major domains of individual differences in human behavior: cognitive abilities, personality, social attitudes, psychological interests, and psychopathology (Lubinski, 2000). In this article we: discuss a number of methodological errors commonly found in research on human individual differences; introduce a broad framework for interpreting findings from contemporary behavioral genetic studies; briefly outline the basic quantitative methods used in human behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

48
484
1
11

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 717 publications
(565 citation statements)
references
References 240 publications
48
484
1
11
Order By: Relevance
“…The results further indicated that the influence of common environmental influences was rather small (14% and 15% for women and men, respectively). This is in line with past research showing that shared environments often do not have a strong influence on phenotypic differences in personality traits (Bouchard, 1998;Bouchard & McGue, 2003). For both men and women, the bulk of the variance was due to unshared environmental factors (E) unique to each individual twin.…”
Section: Heritability Estimatessupporting
confidence: 91%
“…The results further indicated that the influence of common environmental influences was rather small (14% and 15% for women and men, respectively). This is in line with past research showing that shared environments often do not have a strong influence on phenotypic differences in personality traits (Bouchard, 1998;Bouchard & McGue, 2003). For both men and women, the bulk of the variance was due to unshared environmental factors (E) unique to each individual twin.…”
Section: Heritability Estimatessupporting
confidence: 91%
“…It is possible that this abnormal hormonal response is inherited as part of the trait of neuroticism and/or extraversion. There is evidence that temperament and personality, including neuroticism and extraversion, have a substantial heritable component (Bouchard and McGue, 2003;Jang et al, 1996) and may account for as much as 30-60% of the observed variance of such traits (Loehlin, 1993). Similarly, cortisol responses to stress show significant heritability (Federenko et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…1 Enhanced knowledge of personality variables (whether formal diagnostic categories or dimensional traits) can hypothetically contribute to our understanding of the clinical presentation, course, and mechanisms of psychiatric disorders and foster the design of optimal treatment interventions.…”
Section: Introductionmentioning
confidence: 99%